High-sensitivity protein solid-state NMR spectroscopy. (October 2019) - Mandala, Venkata S; Hong, Mei
Highlights: 1 H-detected NMR experiments under fast MAS increase the detection sensitivity compared to 13 C-detected SSNMR experiments. 1 H-detected SSNMR allows structure determination of large proteins in physiological conditions. Dynamic nuclear polarization from electrons to nuclei at cryogenic temperatures increases the nuclear spin polarization by two orders of magnitude. DNP MAS-NMR allows structural studies of large membrane protein complexes, protein intermediates, and proteins in vivo . Abstract : The sensitivity of solid-state nuclear magnetic resonance (SSNMR) spectroscopy for structural biology is significantly increased by 1 H detection under fast magic-angle spinning (MAS) and by dynamic nuclear polarization (DNP) from electron spins to nuclear spins. The former allows studies of the structure and dynamics of small quantities of proteins under physiological conditions, while the latter permits studies of large biomolecular complexes in lipid membranes and cells, protein intermediates, and protein conformational distributions. We highlight recent applications of these two emerging SSNMR technologies and point out areas for future development.